Adult plant resistance in some Indian wheat genotypes and postulation of leaf rust resistance genes - SUBODH KUMAR; D. DATTA, S.C. BHARDWAJ*, M. PRASHAR, S.K. JAIN (Indian Phytopathology, 2010)
Advanced breeding lines and released/identified varieties of wheat were screened against different pathotypes of Puccinia triticina for leaf rust resistance both at seedling as well as adult plant stage in controlled polythene house conditions. Different combinations of seven resistance genes , viz. Lr1, Lr3, Lr10, Lr13, Lr23, Lr26 and Lr34 were characterized by applying the gene matching technique in 39 wheat lines that showed race-specific adult plant resistance (APR) to one and/or the other pathotypes. APR of both hypersensitive and non-hypersensitive types was observed. Varieties GW 322 ( Lr13+) and NIAW 34 ( Lr13+ 34+) showed APR to the three most pathogenic and virulent pathotypes 1R5 (12-2), 121R63-1(77-5) and 21R55(104-2). Twenty-one wheat lines/varieties showed APR to only two pathotypes. The remaining 16 lines showed APR to only one of the three pathotypes. Such race-specific adult plant resistance would be useful in breeding for leaf rust resistance. The seedling and adult plant resistance of these lines can be useful in increasing genetic diversity and avoiding leaf rust epiphytotics on wheat.